Body image perception and dieting practices among overweight and obese adults at Kampong Tebakang Melayu, Serian, Sarawak - Faezatul Akmal, binti Hamidi (Faculty of Medicine & Health Sciences, 2008)
This descriptive study was conducted at Kampung Tebakang Melayu to determine the dieting practices of the respondents, to identify the level of anxiety on body image as well as to determine the relationship between body image with dieting practices and stages of change. Fifty overweight and obese adult aged ranged 18 to 60 years old participated in this study. Data was collected through interviews using questionnaires, anthropometry data were obtained by weighing scale and measuring tape. Data was analyzed using Statistical Package for Social Science (SPSS) version 15.0